IoT Based Real Time Monitoring System For CNC Machine - Tan, Wei Sheng; Yusof, Yusri (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In the era of Industry 4.0, integrating and implementing Internet of Things (IoT) technologies into manufacturing processes is critical for increasing efficiency and reducing machine failures. This study addresses the lack of real-time monitoring systems in CNC machines by focusing on critical parameters such as temperature, humidity, and vibration, all of which are essential for maintaining CNC operations’ precision and efficiency. In this study, the Arduino Mega and NodeMCU ESP8266 microcontrollers are used as primary data acquisition and transmission units. Data is collected using advanced sensors such as the DHT22 for temperature and humidity, and the ADXL-345 for vibration. The collected data is presented in real time via the MATLAB and Blynk. The results of this study show that the percentage of error for temperature and humidity is 0.8789% and 2.1165% respectively. Comparing the maximum and minimum values across five data sets throughout the facing process revealed slight temperature variations, with a maximum of 34.3°C and a minimum of 33.5°C. The humidity levels varied more significantly, ranging from 67.7% to 72.8%. The vibration data showed significant variations: the x-axis ranged from -2.28 m/s² to 0.35 m/s², the y-axis from -0.43 m/s² to 2.28 m/s², and the z-axis from 7.76 m/s² to 12.20 m/s². This study highlights the importance of real-time monitoring in CNC machine and provides a cost-effective IoT-based real-time monitoring solution for CNC machines.